The theory–practice gap in Islamic religious education: A case study of students’ learning difficulties and instructional solutions - Ristiani, Ririn; Zarkasih, Z.; Vebrianto, Rian (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The phenomenon of mismatch between theory and practice in the learning process is still a problem frequently found in educational units. This study aims to describe and analyze the phenomenon of misalignment between theoretically planned learning concepts and the implementation of learning in schools. The method in this study uses a mixed method approach with a case study design. The subjects of this study involved 30 students and 2 teachers. The instruments used in the study consisted of questionnaires and interviews. Data collection was carried out directly in the field through FGD (Focus Group Discussion). The data obtained were analyzed quantitatively and qualitatively so that the results obtained were comprehensive. The results of this study indicate that the level of student understanding of Islamic Religious Education theory and practice is in the very high category with an average score of 4.68. However, this understanding has not been fully implemented in daily behavior, thus indicating a gap between the cognitive, affective, and psychomotor aspects. It can be concluded that Islamic Religious Education learning still tends to be oriented towards theoretical aspects rather than real practice. Therefore, this study provides recommendations in the form of improving teacher competency, developing holistic learning evaluations, and strengthening the role of the environment in supporting the internalization of Islamic Education values. Abstrak Fenomena ketidaksesuaian antara teori dan praktik dalam proses pembelajaran masih menjadi permasalahan yang sering ditemukan di satuan pendidikan. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis fenomena tidak sejalannya antara konsep pembelajaran yang direncanakan secara teoritis dengan pelaksanaan pembelajaran di sekolah. Metode dalam penelitian ini menggunakan pendekatan mix metod (campuran) dengan desain studi kasus. Subjek penelitian ini melibatkan 30 orang siswa dan 2 orang guru. Instrumen yang digunakan dalam peneltian terdiri dari angket dan wawancara. Pegambilan data dilakukan secara langsung turun ke lapangan dengan melakukan FGD (Focus Group Discussion). Data yang di peroleh di analisis secara kuantitatif dan kualiatif sehingga hasil yang didapatkan komprehensif. Hasil dari penelitian ini menunjukkan bahwa tingkat pemahaman siswa terhadap teori dan praktik PAI berada pada kategori sangat tinggi dengan nilai rata-rata 4,68. Namun demikian, pemahaman tersebut belum sepenuhnya diimplementasikan dalam perilaku sehari-hari, sehingga menunjukkan adanya kesenjangan antara aspek kognitif, afektif, dan psikomotorik. Dapat disimpulkan bahwa pembelajaran PAI masih cenderung berorientasi pada aspek teoritis dibandingkan praktik nyata. Oleh karena itu, penelitian ini memberikan rekomendasi berupa peningkatan kompetensi guru, pengembangan evaluasi pembelajaran yang holistik, serta penguatan peran lingkungan dalam mendukung internalisasi nilai-nilai PAI.